Economic crises and energy use: An input–output analysis of Catalonia's 2008–2014 financial crisis - Jaume Freire-González; Oliver Canosa (Journal of Industrial Ecology, 2024)
The impact of economic crises on an economy's energy consumption, considering its sectorial interactions, remains an unexplored area. For this article, we investigated the structural sectorial relationships in energy terms before, during, and after Catalonia's 2008–2014 financial crisis, using environmentally extended input–output analysis. We used three input–output tables from 2005, 2011, and 2014, for which we constructed and employed five vectors representing sectorial energy consumption (“natural gas,” “coal,” “petroleum,” “electricity,” and “biomass and waste”) for 41 economic sectors. We studied the evolution of backward and forward linkage coefficients in terms of energy, as well as key sectors over this period. Our findings reveal that most sectors, particularly energy-intensive ones, experienced a reduction in both backward and forward linkages. However, the relative importance of sectors in the Catalan economy remained relatively stable over the years, indicating a certain level of persistence in this indicator throughout the period, despite the economic crisis.
Keywords: 330